2021
DOI: 10.1038/s41561-021-00797-y
|View full text |Cite
|
Sign up to set email alerts
|

Carbon concentration increases with depth of melting in Earth’s upper mantle

Abstract: Carbon in the upper mantle controls incipient melting of carbonated peridotite and so acts as a critical driver of plate tectonics. The carbon-rich melts that form control the rate of volatile outflux from the Earth's interior, contributing to climate evolution over geological times. However, attempts to constrain the carbon concentrations of the mantle source beneath Oceanic Islands and Continental Rifts is complicated by pre-eruptive volatile loss from magmas. Here, we compile literature data on magmatic gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 104 publications
(183 reference statements)
4
31
0
Order By: Relevance
“…The results show that no correlation exists between the probability of metasomatism and rock type, including clinopyroxenite, dunite, harzburgite, lherzolite, peridotite, pyroxenite, and wehrlite (Figure S6 in Supporting Information S1). Indeed, it has been suggested that metasomatism may occur in various tectonic settings (Aiuppa et al., 2021; Dawson, 1984; Liu et al., 2021; Menzies & Murthy, 1980; Roden & Murthy, 1985; Wang et al., 2022). In particular, carbon and water lower the melting temperatures of peridotites, and carbonated and hydrous silicate melts have been suggested as effective metasomatic agents (Dasgupta & Hirschmann, 2006; Hirschmann, 2000; Sarafian et al., 2017; Sun & Dasgupta, 2019; Thomson et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that no correlation exists between the probability of metasomatism and rock type, including clinopyroxenite, dunite, harzburgite, lherzolite, peridotite, pyroxenite, and wehrlite (Figure S6 in Supporting Information S1). Indeed, it has been suggested that metasomatism may occur in various tectonic settings (Aiuppa et al., 2021; Dawson, 1984; Liu et al., 2021; Menzies & Murthy, 1980; Roden & Murthy, 1985; Wang et al., 2022). In particular, carbon and water lower the melting temperatures of peridotites, and carbonated and hydrous silicate melts have been suggested as effective metasomatic agents (Dasgupta & Hirschmann, 2006; Hirschmann, 2000; Sarafian et al., 2017; Sun & Dasgupta, 2019; Thomson et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Metasomatism modifies the mineralogy and composition of pre‐existing rocks through reaction with melt/fluid at high temperature. This important process produces geochemical and isotopic heterogeneities within Earth's mantle (Aiuppa et al., 2021; Roden & Murthy, 1985; Wang et al., 2022; Zhang et al., 2009), which in turn affect chemical differentiation in the mantle, craton stability, and the physical properties of the lithosphere (Araújo et al., 2009; Dawson, 1984; Liu et al., 2021; Lloyd & Bailey, 1975; Menzies & Murthy, 1980; O’Reilly & Griffin, 2013; Pearson et al., 2021; Peng et al., 2021; Rudnick et al., 1993). Therefore, evaluating mantle metasomatism at the global scale is essential to understanding mantle heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…The dashed gray lines, referred as "H 2 S/SO 2 re-equilibration," describe the evolution of the uprising magmatic gas while its SO 2 /H 2 S ratio re-equilibrates (at constant CO 2 /S T and redox at ΔNNO = −0.75) during decompression from 50 to 60 MPa (magmatic sill) down to 0.1 MPa. Intraplate-continental rift magmatic gases (white circles) range from C-rich to C-poor, depending on the C-enriched or C-depleted signature of their mantle source (Aiuppa et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…
Magmatic gas delivered by intraplate, hot-spot related volcanism offers important insight into the abundance and distribution of volatiles in the Earth's upper mantle (Aiuppa et al, 2021) and hence into the rates and mechanisms of volatile exchange in and out our planet (Dasgupta & Hirschmann, 2010). Hot-spot magmatic gases have long been recognized (Gerlach, 1982;Symonds et al, 1994) to exbibit CO 2 -richer (and H 2 O-poorer) compositions relative to arc magmatic gases (Fischer, 2008;Fischer & Chiodini, 2015;Oppenheimer et al, 2014;Taran & Zelenski, 2015), attesting for the presence of a carbon-rich mantle reservoir (Aiuppa et al, 2021, and references therein) at depths higher than the shallow (<50 km) Depleted Mantle (DM) sampled by MORBs (Mid-Ocean Ridge Basalts;Hauri et al, 2019).
…”
mentioning
confidence: 99%
See 1 more Smart Citation